Kepemimpinan Birokrasi Pelayanan Publik (Studi atas Perilaku dan Motif Elit Birokrasi Dinas Perijinan Kota Malang dalam Mewujudkan Pelayanan Prima) - -, Suryadi (Universitas Brawijaya, Indonesia, 2009)
Bureaucracy elites as leaders play a very important role in determining a quality of public services. This research sought to understand: 1) The behavior of Bureaucracy Elites in giving public service. 2) Motive of their behavior and 3) quality of their service. This research show that the behavior of bureaucracy elites are expressed by some decisions and actions which show discriminative behavior such as giving special service to the ruling group of society with motive to save their position, allowing the staff to give special service to the haves with motive to get more money and loyalty of their staff, and giving excellent service to all groups of society , especially in arranging for trivial matters with motive to get pride and as sacrifice. As the impact of their discriminative behavior, bureaucracy elites can not perform excellence service.Keywords: behavior, motive, bureaucracy, bureaucracy elites, public services, service exellence.